2019
DOI: 10.1080/08039488.2018.1536766
|View full text |Cite
|
Sign up to set email alerts
|

Association between prescribed antidepressants and other prescribed drugs differ by gender: a nationwide register-based study in Sweden

Abstract: Background: People with depression are prescribed more drugs than people in general, partly due to comorbidity with other conditions. However, little research has been done on depression-related drug use from a gender perspective. Aim: Examine the association between antidepressants, other types of prescribed drugs, and polypharmacy, by gender. Methods: Data on drugs dispensed October to December 2016 to all Swedish citizens aged 18-84 years were collected from the Swedish prescribed drug register. Logistic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 71 publications
2
5
0
Order By: Relevance
“…Gender differences can also be seen in the prescription of antidepressants, where women are dominant. This observation is consistent with the fact that women are more often diagnosed with depression and may even be over diagnosed [10,11], whereas men risk being underdiagnosed. It is of note that these differences may be due, at least in part, to the screening tools used because they are designed for female expressions of depression, whereas men exhibit other symptoms [11].…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…Gender differences can also be seen in the prescription of antidepressants, where women are dominant. This observation is consistent with the fact that women are more often diagnosed with depression and may even be over diagnosed [10,11], whereas men risk being underdiagnosed. It is of note that these differences may be due, at least in part, to the screening tools used because they are designed for female expressions of depression, whereas men exhibit other symptoms [11].…”
Section: Introductionsupporting
confidence: 88%
“…This observation is consistent with the fact that women are more often diagnosed with depression and may even be over diagnosed [10,11], whereas men risk being underdiagnosed. It is of note that these differences may be due, at least in part, to the screening tools used because they are designed for female expressions of depression, whereas men exhibit other symptoms [11]. Previous research suggests that symptoms in men might instead manifest through irritableness, anger, addiction, and flight behaviour [12].…”
Section: Introductionsupporting
confidence: 88%
“…This study revealed that the prevalence of polypharmacy is higher in women. A nationwide study from Sweden has shown that psychiatric polypharmacy among women was higher than men [ 26 ]. Other studies have shown that the prevalence of polypharmacy among women, regardless of their status regarding depression, is higher than men [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…al. [ 26 ] have shown that among women with DD, drugs related to the genitourinary system were the 3rd common prescribed drug class. Psychiatrists may also need to consider asking about genitourinary diseases from female patients and adopt the therapeutic approaches that they chose.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] With respect to sex and age, some studies indicate that GPs prescribe more depression drug therapy to women and older people than to men and younger people. 14,15 However, there is a lack of studies that use a new depression diagnosis to confirm this trend.…”
Section: Introductionmentioning
confidence: 99%